Application of Air Deck Method to Reduce the Impact of Ground Vibration and Optimization of Limestone Fragment Size in Blasting Activities at PT Semen Baturaja (Persero), Tbk. - Arief, Taufik; Purbasari, Diana; Intan, Aliyah (Ridwan Institute, 2023)
The field experiment of applying the air deck method to the limestone blasting activities of PT Semen Baturaja (Persero), aims to reduce the impact of ground vibration considering that mining activities are approaching residential areas. In addition, the size of the fragmentation of the blasting results is very important for the effectiveness of the crushing plant. To determine the effectiveness of the application of the air deck method in limestone mining (quarry), blasting planning activities are carried out by dividing the two blasting locations, namely blasting with the air deck method and without using an air deck. By using a zig-zag blasting pattern and the number of holes of 50 Lb, the depth of the drill holes is 9 meters (without air deck) and 13 meters and the type of explosive used is Nonel. From the results of the analysis of limestone blasting with data processing using the split desktop 2.0 demo application, the ground vibration value (micromater system) was obtained. The average value of ground vibration (pVS) shows a smaller value using the air deck method of 0.68 mm/sec while without air deck of 0.74 mm/sec. The results of limestone fragmentation analysis with the air deck method obtained size <75cm reached 91.93%, while for without air deck it was 80.27%. These results show that the air deck method can be applied as a method to assist the Company in reducing ground vibration and limestone fragmentation effectively and efficiently by considering natural factors including geographical factors.